Pengembangan Bahan Ajar Terintegrasi Dengan Pendidikan Karakter Pada Mata Pelajaran Bahasa Indonesia SD Kelas IV - Galih Kusumo (Universitas Tidar, 2017)
This study was research and development. This research and development was based on unavailibility of Indonesian language teaching materials based on the character value. Whereas, it is very essential and important for primary students to develop their character. This research was aimed at developing a product in form of Indonesian language teaching material which was integrated with character value. The development of the product in this study was done by combining steps from Kemps model and Borg and gall consisting of: (1) potential and problems, (2) data collection, (3) design product (prototype) (4) validation, (5) product revision (6) main field testing, (7) revision. The result of this research revealed that the product was good and proper to be used to teach Indonesian language in primary school grade 4.Keywords: character education, teaching materials, development model